2005
DOI: 10.1111/j.1399-6576.2004.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline attenuates the increase in whole blood viscosity after transfusion

Abstract: These results suggest that pentoxifylline is effective in attenuating the increase in whole blood viscosity after a transfusion of packed red-blood cells. Plasma viscosity is not influenced by pentoxifylline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…PTX increases erythrocyte deformability, decreases platelet aggregation and decreases fibrinogen levels. 25,26 Furthermore, in an animal model, PTX was associated with increasing fibrinolytic activity in the peritoneum leading to a decrease in formation of peritoneal adhesions. 27 This may be relevant to PD as it has been shown that fibrin can induce PD-like lesions in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…PTX increases erythrocyte deformability, decreases platelet aggregation and decreases fibrinogen levels. 25,26 Furthermore, in an animal model, PTX was associated with increasing fibrinolytic activity in the peritoneum leading to a decrease in formation of peritoneal adhesions. 27 This may be relevant to PD as it has been shown that fibrin can induce PD-like lesions in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The other replacement of the N-1-(CH 2 ) 4 COCH 3 group, as in the case of compound S6c, also showed an effective 50% and 77% inhibition of TNF-α and IL-8 production in LPS-stimulated Raw 264.7 and HK-2 cells. flexibility, reducing blood viscosity [1], and decreasing the potential for platelet aggregation [15].…”
Section: Introductionmentioning
confidence: 99%
“…The current authors have previously shown that the methylxanthine derivative pentoxifylline reduces alveolar fibrin deposition and vascular alveolar leakage, and prolongs survival in rats with neonatal hyperoxic lung injury [5], a suitable in vivo model for experimental BPD [6]. Pentoxifylline can exert its protective effect in inflammatory lung diseases in different ways, including: inhibition of vascular leakage; improved vascular blood flow by reducing blood viscosity and improving red blood cell flexibility by increasing membrane fluidity; and inhibition of leukocyte activation [7][8][9]. The protective effects in inflammatory lung diseases have been partially ascribed to the weak nonselective inhibition of PDEs by pentoxifylline, resulting in increased intracellular cAMP levels [10,11].…”
mentioning
confidence: 99%